Concept of digital health literacy revisited: Using text network and topic model analysis - Jiyoung Park; Seohyun Won; Mingee Choi; Chul Hee Kang; Han Shi Jocelyn Chew (Digital Health)
Background The rapid integration of ICT into healthcare has elevated the critical role of digital health literacy (DHL). However, the conceptual relationship between DHL and electronic health (eHealth), along with the impact of transformative events such as the Fourth Industrial Revolution and the COVID-19 pandemic, remains inadequately investigated. Objective This study seeks to analyze research trends in DHL across four distinct historical periods to uncover key themes and their temporal evolution. Methods A comparative analysis of 2645 abstracts from Scopus publications (1977–2022) was conducted, segmented into four periods: (I) emerging era (1977–2006), (II) establishment era (2007–2016), (III) diffusion era (2017–2020), and (IV) post-pandemic era (2021–present). Text network analysis identified core keywords, and Latent Dirichlet Allocation (LDA) extracted dominant topics and their temporal evolution. Results Since 2006, DHL research has exhibited consistent growth, underpinned by transformative advancements during the Fourth Industrial Revolution and further amplified by a significant surge in scholarly engagement in the post-pandemic era. Importantly, during the diffusion era (Period III), a divergence in the trajectories of “digital health literacy” and “electronic health literacy” emerged. Text network analysis revealed a progression toward greater uniformity in node sizes over time, coupled with an increase in the complexity and intricacy of connections between nodes. These findings indicate a growing diversity and nuanced understanding of concepts associated with DHL. Moreover, research in the post-pandemic era (Period IV) emphasized the critical role of DHL in addressing health disparities and advancing equitable access to healthcare. Conclusion The study reveals the dynamic progression of DHL research, catalyzed by technological advancements and global health crises. Strengthening DHL, particularly among vulnerable populations, is crucial for mitigating health disparities in a rapidly digitalizing world. Future research should prioritize the development of targeted interventions and examine DHL's impact across diverse sociocultural contexts.